Hemisection of fused teeth involving a maxillary permanent incisor and a supernumerary tooth. Issue 3 (December 2015) - Zheng, Jiajia; Shinonaga, Yukari; Kawai, Saki; Abe, Yoko; Harada, Kyoko; Arita, Kenji
Abstract: Purpose: Fusion is the union of adjacent teeth with or without pulp involvement. It can lead to serious esthetic problems and malocclusion. Here we report two rare cases of fusion of a permanent maxillary incisor with a supernumerary tooth that we successfully corrected using hemisection, which was performed after we confirmed that the roots had developed and separated. Case reports: In the first case, the whole vital pulp was preserved. In the second case, partial pulpotomy was performed. Conclusion: The differential diagnosis and appropriate management of permanent anterior fused teeth are essential to attain a favorable outcome and minimize the risk of any complications.